Opportunities and barriers to portable document scanning - Brown, Barry A. T.; Sellen, Abigail; O'Hara, Kenton (Personal Technologies: Special Issue on Human-Computer Interaction with Mobile Devices, 2000)
While electronic documents are increasingly prevalent in the workplace there are many texts – such as books, magazines and letters – which are not easily available in an electronic form. Since many electronic document systems depend upon documents existing exclusively, or at least predominantly, in electronic form, this suggests an opportunity for document scanning technology. However, conventional scanners are limited by their large size and relatively cumbersome usage. Using a diary-based methodology, this study investigated the use of a new portable document scanning technology. In this paper we explore the need for document scanning, and how this portable device was used by our study participants. Document scanning is shown to be a goal-driven activity – individuals did not scan just to have an electronic version of a document, but to do something with electronic documents, in particular, distributing documents to others, archiving documents and reusing documents. The small design of this device also enabled a mode of usage distinct from that of conventional flatbed scanners. Its size meant that the device was a personal, rather than shared technology; that it could be easily stored when not being used; and that the scanner could be carried to the materials to be scanned, rather than the materials brought to the scanner. We discuss this interaction with the local environment as a case of “local mobility” – this is less to do with portability but with how a device’s small size can make it fit better into work environments.